Trajectories of disease courses in the inception cohort of newly diagnosed patients with JIA (ICON-JIA): the potential of serum biomarkers at baseline - Margarita Ganeva; Sabrina Fuehner; Christoph Kessel; Jens Klotsche; Martina Niewerth; Kirsten Minden; Dirk Foell; Claas H. Hinze; Helmut Wittkowski (BMC, 2021)
Abstract Objective Juvenile idiopathic arthritis (JIA) is a heterogeneous group of inflammatory joint disorders with a chronic-remitting disease course. Treat-to-target approaches have been proposed but monitoring disease activity and predicting the response to treatment remains challenging. Methods We analyzed biomarkers and their relationship to outcome within the first year after JIA diagnosis in the German Inception Cohort of Newly diagnosed patients with JIA (ICON-JIA). CRP, CXCL9, CXCL10, CXCL11, erythrocyte sedimentation rate, G-CSF, IL-6, IL-17A, IL-18, MCP-1, MIP-1α, MMP-3, S100A8/A9, S100A12, TNFα, and TWEAK were measured at baseline and 3 months later. Results Two-hundred-sixty-six JIA patients with active disease at baseline were included, with oligoarthritis and rheumatoid factor-negative polyarthritis representing the most frequent categories (72.9%). Most biomarkers were elevated in JIA compared to healthy pediatric controls. Patients with systemic JIA had higher CRP, S100A8/A9 and S100A12 levels compared to other JIA categories. Baseline levels of TWEAK, G-CSF and IL-18 were lower in oligoarthritis patients with disease extension within 1 year. Increased baseline levels of CRP, S100A8/A9, S100A12 and ESR were associated with the subsequent addition of biologic disease-modifying antirheumatic drugs (DMARDs). Higher baseline ESR, G-CSF, IL-6, IL-17A and TNF levels indicated an increased risk for ongoing disease activity after 12 months. Conclusion Our data demonstrate that elevated baseline levels of CRP, S100A8/A9 and S100A12 as well as increased ESR are associated with the necessity to escalate therapy during the first 12 month of follow-up. Furthermore, biomarkers related to Th17 activation may inform on future disease course in previously treatment-naïve JIA patients.